Estimation of salivary pH, buffering capacity, flow rate, caries prevalence and oral manifestation in chronic renal failure patients undergoing dialysis - Ojha, Bidhata; Baral, Radha; Bajracharya, Dipshikha (Journal of Chitwan Medical College, 2020)
Background: Renal failure is a process that expresses a loss of functional capacity of the nephrons, independently of its etiology. Although acute renal failure is reversible in the majority of cases, chronic renal failure presents a progressive course towards terminal renal failure. Hemodialysis is the most widely used technique leading to systemic alterations, oral complications and variations in the flow and composition of the saliva. The purpose of this study was to estimate salivary pH, buffering capacity, flow rate in chronic renal failure patients undergoing hemodialysis with its oral manifestation and caries prevalence. Methods: Saliva samples were collected from 40 patients with chronic renal failure undergoing dialysis and 40 healthy subjects after taking the informed consent. Saliva samples were then taken to the lab for processing. Salivary pH, buffering capacity and flow rate was estimated. DMFT was calculated. The statistical analysis was done using SPSS version 23. Results: A statistically significant rise in salivary pH, buffering capacity with decrease in flow rate was noted in chronic renal failure patients undergoing dialysis compared to controls. Furthermore, decrease in DMFT value was noted in CRF group despite of poor oral hygiene of the patient. We could also observe different oral manifestations in CRF group among which uremic fetor being the commonest. Conclusions: Our report suggest that saliva is noninvasive tool which act as an adjunct in diagnosing oral lesions and manifestations in CRF patients whose oral hygiene is often neglected with their reluctance in long term dental appointment in the middle of regular hemodialysis schedule.